Elio Chinol narratore, riproposto da Peppino Grossi - Grilli, Giuseppe (Dialogoi. Rivista di studi comparatistici, 2020)
The article reprints the critical contribution by Peppino Grossi which appeared in Studium in 1975 relating to a novel, La vita perduta, perhaps the elder, by Elio Chinol, an English anglist from Treviso who taught in Naples for a long time and traces of the generation of Neapolitan writers of the sixties and later; the revival is introduced by Giuseppe Grilli's note which contextualizes the gestation of the book and also its posterity, also linking it to a choice of Anglo-born Chinol, in particular the letters and interpreter of Shakespeare's sonnets.